1990
DOI: 10.1212/wnl.40.12.1900
|View full text |Cite
|
Sign up to set email alerts
|

Acute axonal polyneuropathy associated with anti‐GM 1 antibodies following Campylobacter enteritis

Abstract: We report 2 patients with Guillain-Barré syndrome (GBS) following Campylobacter jejuni enteritis. Electrophysiologic studies indicated that the predominant process was axonal degeneration of motor nerves, and clinical recovery was poor. Serum testing by thin-layer chromatography and enzyme-linked immunosorbent assay revealed that the sera from both patients contained high titers of IgG antibody against GM1 ganglioside. These cases may represent a subgroup of GBS as acute axonal polyneuropathy following C jejun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
188
1
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(199 citation statements)
references
References 0 publications
6
188
1
4
Order By: Relevance
“…In contrast, the anti-GM1 IgG titers correlated with the disease onset in the inoculated rabbits and in the GBS patients (5). The inflammatory response in GBS may be triggered by either activation of complement or leukocytes.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, the anti-GM1 IgG titers correlated with the disease onset in the inoculated rabbits and in the GBS patients (5). The inflammatory response in GBS may be triggered by either activation of complement or leukocytes.…”
Section: Discussionmentioning
confidence: 84%
“…Ganglioside GM1 is an autoantigen for IgG Abs in patients with axonal GBS subsequent to C. jejuni enteritis (2,5). C. jejuni strains isolated from such patients have a lipooligosaccharide (LOS) with a GM1-like structure (2,6).…”
mentioning
confidence: 99%
“…Elevated researches showed that Campylobacter jejuni was closely related to the GBS (Koga, Yuki, & Hirata, 1999; Odaka, Koga, Yuki, Susuki, & Hirata, 2003; Ogawara et al., 2000; Zhang et al., 2010, 2015). Furthermore, serials of investigations indicated that AGA can be found in the serum of patients with CMV‐IgG positive (Caudie et al., 2002; Sivadon et al., 2005; Yuki, Yoshino, Sato, & Miyatake, 1990). Meanwhile, Simanek AM and co‐workers provided evidence that the CMV reaction had the relationship with chronic inflammation (Simanek et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Serum anti-ganglioside antibodies have been assayed by thin-layer chromatography (TLC) or enzyme-linked immunosorbent assay (ELISA) in patients with Guillain-Barre syndrome (GBS), and its variant Miller Fisher syndrome (MFS) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). As a result of this prevalence, it is known that some types of anti-ganglioside antibodies are specifically linked with the antecedent events or clinical features in GBS.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this prevalence, it is known that some types of anti-ganglioside antibodies are specifically linked with the antecedent events or clinical features in GBS. Serum IgG anti-GMl antibodies with or without anti-GDIb antibodies, which are often present after Campylobacter jejuni enteritis (3,(13)(14)(15), sometimes cause acute motor axonal (AMAN) or motor and sensory axonal neuropathy (AMSAN) (16,17). IgM anti-GM2 antibodies occur in patients, frequently associated with facial palsy and sensory neuropathy, with an antecedent CMVinfection (9,18,19).…”
Section: Introductionmentioning
confidence: 99%